Reading in medieval St. Gall - Grotans, Anna A., 1961- (Cambridge studies in palaeography and codicology, 2006)
Learning to read in medieval Germany meant learning to read and understand Latin as well as German. The manuscripts of the tenth-century scholar and teacher Notker Labeo display how the medieval pedagogic method combined Latin and vernacular literacy. This study has much to contribute to our knowledge of medieval reading.